Prenatal care in public health services in the State of Paraná (Research, Society and Development, 2021)
Objective: to analyze prenatal care in public services of three Health Regional in Paraná. Methodology: cross-sectional, descriptive, quantitative, cut from a prospective cohort, performed in health services of the 9th, 10th. and the 17th Regional from July 2017 to March 2018, with 1,211 women. Maternal medical records, pregnant women card and instrument with socioeconomic and demographic data, and prenatal variables were used, grouped, and analyzed statistically in the SPSS v20.0 program. Results: predominance of women between 19 and 34 years old (78.1% in the 9th, 80.5% in the 10th and 77.6% in the 17th); family income of 1 to 3 minimum wages (67.8% on the 9th, 62.9% on the 10th and 63% on the 17th); 99% adhered to prenatal care in the 3 Regional, beginning within 14 weeks (81.6% on the 9th, 69.6% on the 10th and 79.0% on the 17th); 80% of pregnant women had 6 or more consultations, with the usual risk classification (65.5% on the 9th, 62.8% on the 10th and 53.1% on the 17th); low rates of referrals to specialized services (14.9% on the 9th, 27.5% on the 10th and 28.7% on the 17th), with a waiting time longer than 29 days on the 17th (47.2%); in the 17th, low performance of oncotic cytology and dental consultation stands out, with only 59.5% and 63.2%, respectively. Conclusion: prenatal care in public health services, in general, meets the requirements of the Ministry of Health, however, it is necessary that managers provide assertive training to the professionals involved, for the proper implementation of national protocols aiming at positive outcomes of the pregnancy-puerperal period.